Consecutive Slides on Axial View Is More Effective Than Transversal Diameter to Differentiate Mechanisms of Single Subcortical Infarctions in the Lenticulostriate Artery Territory - Cao, Yuze; Zhang, Mengyu; Zhou, Lixin; Yao, Ming; Peng, Bin; Zhu, Yicheng; Ni, Jun; Cui, Liying (Frontiers in Neurology, 2019)
Objective Lipohyalinosis or atherosclerosis might be responsible for single subcortical infarctions (SSIs); however, ways of differentiating between the two clinically remain uncertain. We aimed to investigate whether longitudinal diameter (slices) or transversal diameter is more effective to differentiate mechanisms by comparing their relationships with white matter hyperintensities (WMHs). Methods All the participants from the Standard Medical Management in Secondary Prevention of Ischemic stroke in China (SMART) cohort who had SSIs in the lenticulostriate artery territory were included and categorized according to longitudinal slices (≥4 consecutive slices or not) and transversal diameter (≥15 mm or not). The associations between the severity of WMHs and the different categories were analyzed. Results Among the 3821 patients of the SMART study, 282 had diffusion-weighted image-proven SSIs in the lenticulostriate artery territory. When classified by longitudinal slices, SSIs on ≥4 slices were significantly associated with the severity of the WMHs, both in deep WMH (DWMH) (odds ratio [OR], 0.32; 95% confidence interval [CI], 0.11–0.97; p = 0.04) and periventricular hyperintensity (PVH) (OR, 0.37; 95% CI, 0.17–0.78; p = 0.01). No such association was found on the basis of the transversal diameter (p > 0.1). Conclusion Longitudinal slices (≥4 consecutive slices) might be more effective than transversal diameter to identify the atherosclerotic mechanisms of SSIs in the lenticulostriate artery territory.